2012
DOI: 10.1167/iovs.11-8762
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Biofilm Diversity in Contact Lens-Related Disease: Emerging Role ofAchromobacter,Stenotrophomonas, andDelftia

Abstract: PURPOSE. Multi-species biofilms associated with contact lens cases and lenses can predispose individuals to contact lensrelated inflammatory complications. Our study used cultureindependent methods to assess the relationship between the severity of contact lens-related disease and bacteria residing in biofilms of contact lens cases and lenses.METHODS. Contact lens cases and lenses from 28 patients referred to the West Virginia University Eye Institute and diagnosed as having mild keratitis, keratitis with foca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
88
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 35 publications
4
88
0
1
Order By: Relevance
“…was predominant bacterium in patients with contact lens-related corneal disease, with occurrence of 76% of lens cases. This outcome was in part explained by the ability of Achromobacter to form biofilms on the surface of CL, which was confirmed by SEM analysis [8]. Some studies showed that Achromobacter spp.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…was predominant bacterium in patients with contact lens-related corneal disease, with occurrence of 76% of lens cases. This outcome was in part explained by the ability of Achromobacter to form biofilms on the surface of CL, which was confirmed by SEM analysis [8]. Some studies showed that Achromobacter spp.…”
Section: Discussionmentioning
confidence: 68%
“…Also, a study using scanning electron microscopy (SEM) showed that Achromobacter spp. were able to form biofilms on the surface of CL from patients with microbial keratitis [8]. To the best of our knowledge, there is no data describing the occurrence of A. xylosoxidans as a causative agent of contact lens-associated keratitis as well as a contaminant of contact lens cases in Serbia.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations